Troubling normal in world language education. Issue 2 (3rd April 2019) - Cahnmann-Taylor, Melisa; Coda, James
ABSTRACT: Queer theory problematizes societal norms related to sex, gender, and sexuality, while resisting normalcy. The authors utilize a queer theoretical approach in analysis of participant observation in adult Spanish and Mandarin classes as well as interviews with world language teachers. Analysis of interview data reveals how educators and adult language learners experience gender/sexuality norms in conventional classroom and school contexts. Classroom observations and analysis of classroom discourse identify moments when these norms may be "troubled" or upheld in contexts using a progressive new approach called Teaching Proficiency through Reading and Storytelling (TPRS). Findings suggest that the improvisational nature of TPRS raises complex questions about heteronormativity in language learning and the creative work in which educators and students can engage in dialogic classrooms.